2018
DOI: 10.1038/s41386-018-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine administration during a critical period after forced ethanol abstinence inhibits the development of time-dependent affective disturbances

Abstract: Forced abstinence from chronic two bottle-choice ethanol drinking produces the development of negative affective states in female C57BL/6J mice. We previously reported that this disrupted behavior is acutely reversed by administration of ketamine 30 min-prior to testing. Here we assessed whether ketamine can be used as an inoculant against the development of abstinence- dependent affective disturbances. In parallel, we examined the impact of ketamine administration on long-term potentiation (LTP) in the bed nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…A lack of observable differences in anxiety-like behaviors in the EPM and OFT between control and FAexposed mice in our study could indicate a transition from the heightened anxious state associated with acute withdrawal and early abstinence (Lee et al, 2015; to a more depressive-like state during protracted abstinence (Driessen, 2001;Heilig et al, 2010;Stevenson et al, 2009). Previous studies using the same two-bottle choice paradigm demonstrated that female mice develop a heightened depressive-like behavioral phenotype during protracted abstinence from alcohol, as indicated by longer time spent immobile in the FST and longer latency to feed in the novelty-suppressed feeding test (NSFT), that can be alleviated by physical activity (Pang et al, 2013) or administration of the novel fast-acting antidepressant ketamine (Holleran et al, 2016;Vranjkovic et al, 2018). Interestingly, here we observed a more robust depressive-like behavioral phenotype in the FST in FA-exposed male mice, and not FA-exposed female mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A lack of observable differences in anxiety-like behaviors in the EPM and OFT between control and FAexposed mice in our study could indicate a transition from the heightened anxious state associated with acute withdrawal and early abstinence (Lee et al, 2015; to a more depressive-like state during protracted abstinence (Driessen, 2001;Heilig et al, 2010;Stevenson et al, 2009). Previous studies using the same two-bottle choice paradigm demonstrated that female mice develop a heightened depressive-like behavioral phenotype during protracted abstinence from alcohol, as indicated by longer time spent immobile in the FST and longer latency to feed in the novelty-suppressed feeding test (NSFT), that can be alleviated by physical activity (Pang et al, 2013) or administration of the novel fast-acting antidepressant ketamine (Holleran et al, 2016;Vranjkovic et al, 2018). Interestingly, here we observed a more robust depressive-like behavioral phenotype in the FST in FA-exposed male mice, and not FA-exposed female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that forced abstinence (FA) from alcohol produces depressive-like behavior and a variety of neurobiological changes in rodent models. For instance, Vranjkovic et al (2018) demonstrated that following six weeks of alcohol drinking, female C57BL/6J mice showed decreased time spent in the open arm of the elevated plus maze (EPM), and increased latency to feed in the novelty suppression of feeding test (NSFT), two commonly used models of anxiety-like behavior. In addition, this model produced increased immobility in the forced swim test (FST), though it should be noted males were not investigated in these studies (Holleran et al, 2016;Vranjkovic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AUD is frequently comorbid with affective mood disorders (3,4) and this fact often limits available treatment interventions (5). The negative affective disturbances that tend to develop during abstinence from drinking can drive relapse-like behaviors in both humans and rodent models (6)(7)(8)(9)(10)(11)(12). This is further complicated by preclinical and clinical evidence that links increased alcohol drinking with the use of drugs such as SSRIs that are commonly used to treat depression and anxiety (13,14).…”
Section: Introductionmentioning
confidence: 99%